IgG4-related disease in the Japanese population: a genome-wide association study. (September 2019) - Terao, Chikashi; Ota, Masao; Iwasaki, Takeshi; Shiokawa, Masahiro; Kawaguchi, Shuji; Kuriyama, Katsutoshi; Kawaguchi, Takahisa; Kodama, Yuzo; Yamaguchi, Izumi; Uchida, Kazushige; Higasa, Koichiro; Yamamoto, Motohisa; et al.
Summary: Background: IgG4-related disease is a newly recognised immunopathological entity that includes autoimmune pancreatitis, IgG4-related sialadenitis, and IgG4-related kidney disease. To understand the genetic landscape of IgG4-related disease, we did a genome-wide association study. Methods: We did a genome-wide association study of Japanese individuals, initially screening 857 patients with IgG4-related disease at 50 Japanese research institutions and DNA samples from 2082 healthy control participants from the Nagahama Prospective Genome Cohort for the Comprehensive Human Bioscience. From Oct 27, 2008, to July 22, 2014, we enrolled 835 patients and used data from 1789 healthy participants. Only patients with confirmed diagnosis of IgG4-related disease according to the international diagnostic criteria were included. Genotyping was done with the Infinium HumanOmni5Exome, HumanOmni2.5Exome, or HumanOmni2.5 Illumina arrays, and genomic distributions were compared between case and control samples for 958 440 single nucleotide polymorphisms. The HLA region was extensively analysed using imputation of HLA alleles and aminoacid residues. Fine mapping of the FCGR2B region was also done. Associations between clinical manifestations of disease and the genetic variations identified in these two genes were examined. Findings: We identified the HLA-DRB1 (p=1·1×10 −11 ) and FCGR2B (p=2·0×10 −8 ) regions as susceptibility loci for IgG4-related disease. We also identified crucial aminoacid residues in the β domain of the peptide-binding groove of HLA-DRB1, in which the seventh aminoacid residue showed the strongest association signal with IgG4-related disease (p=1·7×10 −14 ), as has been reported with other autoimmune diseases. rs1340976 in FCGR2B showed an association with increased FCGR2B expression (p=2·7×10 −10 ) and was in weak linkage disequilibrium with rs1050501, a missense variant of FCGR2B previously associated with systemic lupus erythematosus. Furthermore, rs1340976 was associated with the number of swollen organs at diagnosis (p=0·011) and IgG4 concentration at diagnosis (p=0·035). Interpretation: Two susceptibility loci for IgG4-related disease were identified. Both FCGR2B and HLA loci might have important roles in IgG4-related disease development. Common molecular mechanisms might underlie IgG4-related disease and other immune-related disorders Funding: The Japanese Ministry of Health, Labour, and Welfare, the Japanese Agency of Medical Research and Development, and Kyoto University Grant for Top Global University Japan Project.